Flaubert, Beckett, Toussaint : d’un phrasé l’autre - Karine Germoni (Flaubert: Revue Critique et Génétique)
If Flaubert, Beckett and Toussaint are members of what Sainte-Beuve called “a spiritual family”, it is because they share the same sense of irony and humour which is reflected in the way they each treat syntax, style or punctuation. Thus, if on the one hand Flaubert’s presence appears through Beckett’s works, on the other, in Toussaint’s works there is the simultaneous obvious presence both of Beckett and Flaubert. But whereas Beckett voluntarily imitates Flaubert, to honour him, it is involuntarily at first that Toussaint, in his first works, does pastiches of Beckett and Flaubert, before attaining his own writing, an experienced writer’s style where there will remain, as we will see, remnants of flaubertian and beckettian phrases.